2013
DOI: 10.1021/pr3011815
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Proteomic Analysis Identified Paraoxonase 1 as a Novel Serum Biomarker for Microvascular Invasion in Hepatocellular Carcinoma

Abstract: This study aimed to identify serum biomarkers for microvascular invasion (MVI) in hepatocellular carcinoma (HCC). MVI is a histological sign of micrometastasis in the liver and is considered as one of the most powerful prognostic factors in HCC. The serum of HCC patients with different vascular invasion statuses was examined by iTRAQ-based proteomic profiling. The expression levels of 24 proteins were associated with the extent of vascular invasion in the pooled samples of 45 HCC cases. Western blot analyses i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 37 publications
1
28
0
Order By: Relevance
“…To validate the 2D-DIGE results, target proteins underwent Western blotting as reported before Huang et al 25. Briefly, after diluting crude sera 10-fold with Milli-Q water(without depleting abundant proteins) quantitation was carried out and 30 μg of serum were mixed with 5X loading buffer(2 μl) and loaded in each lane of one 12% SDS-PAGE with 4% stacking gel.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To validate the 2D-DIGE results, target proteins underwent Western blotting as reported before Huang et al 25. Briefly, after diluting crude sera 10-fold with Milli-Q water(without depleting abundant proteins) quantitation was carried out and 30 μg of serum were mixed with 5X loading buffer(2 μl) and loaded in each lane of one 12% SDS-PAGE with 4% stacking gel.…”
Section: Methodsmentioning
confidence: 99%
“…2D-DIGE incorporates the use of fluorescent molecules(CyDyes), or fluors, that are used to pre-label samples prior to separation by 2-DE19, being a very sensitive gel-based proteomic technique that is unique through the utilization of fluorescently labelled samples on the same gel, and the application of an internal standard for intra- and inter-gel comparisons and normalization24. This technique has been used for studies of hepatocellular carcinoma25, alterations in human endometriosis26 and patients with diabetes and cardiovascular disease27.…”
mentioning
confidence: 99%
“…MVI is an early means of cancer cell spread via the vasculature [4]. MVI is only visible on microscopy, and it is difficult to be detected before surgical resection [5]. MVI was found to be one of the most important risk factors for intrahepatic recurrence in HCC patients who underwent curative surgery; thus, it may serve as a surrogate marker reflecting tumor biological characteristics [6, 7], and was recognized as an independent predictor of early recurrence and poor overall survival (OS) following liver resection and liver transplantation [810].…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, the isobaric tags for relative and absolute quantitation (iTRAQ) profiling technology enables the quantitative and direct comparison of the proteome changes up to 8 samples simultaneously with very high sensitivity and protein coverage [21,22]. Several groups have reported the application of iTRAQ-based quantitative proteomics approach in the study of hepatic cancer, especially for the screening of diagnostic and prognostic protein biomarkers [23][24][25]. For instance, Huang et al have reported the iTRAQ-based quantitative analysis of the recurrence/metastasis of Huge HCC (diameter is larger than 10 cm) at different stages, and identified two biomarkers for distinguishing and predicting the early recurrence/metastasis behaviors of Huge HCC [26]; Wang et al have reported the serum proteome of metastatic HCC using the iTRAQ-based quantitative analysis and identified a metastasis-associated biomarker [27].…”
Section: Introductionmentioning
confidence: 99%